The use of a Method for Structural Design of Ring-Girders used in Penstocks - Aguilera Chaves, Mónica Gabriela (2025)
The methodology that calculates the internal stresses on a penstock shell restrained by a rigid ring girder was developed since the 1930’s, however, its automatization has not been implemented by commercial use software due to its complexity. This projectintends to automate one methodology to calculate the internal stresses on a steel penstock shellrestrained bya ring-girder. A penstock under normal operation condition, this is apipe full of water under pressure, was analyzed. A calculating tool was produced using EXCEL 2016 and Mathcad 10, for calculating the internal stresseson the penstock’s ring girder cross sections. The tool doesn’t consider the earthquake loading conditions.